Advances in Lithium–Sulfur Batteries: From Academic Research to Commercial Viability. Issue 29 (6th June 2021) - Chen, Yi; Wang, Tianyi; Tian, Huajun; Su, Dawei; Zhang, Qiang; Wang, Guoxiu
Abstract: Lithium‐ion batteries, which have revolutionized portable electronics over the past three decades, were eventually recognized with the 2019 Nobel Prize in chemistry. As the energy density of current lithium‐ion batteries is approaching its limit, developing new battery technologies beyond lithium‐ion chemistry is significant for next‐generation high energy storage. Lithium–sulfur (Li–S) batteries, which rely on the reversible redox reactions between lithium and sulfur, appears to be a promising energy storage system to take over from the conventional lithium‐ion batteries for next‐generation energy storage owing to their overwhelming energy density compared to the existing lithium‐ion batteries today. Over the past 60 years, especially the past decade, significant academic and commercial progress has been made on Li–S batteries. From the concept of the sulfur cathode first proposed in the 1960s to the current commercial Li–S batteries used in unmanned aircraft, the story of Li–S batteries is full of breakthroughs and back tracing steps. Herein, the development and advancement of Li–S batteries in terms of sulfur‐based composite cathode design, separator modification, binder improvement, electrolyte optimization, and lithium metal protection is summarized. An outlook on the future directions and prospects for Li–S batteries is also offered. Abstract : The major developments and advancements of lithium–sulfur batteries over the past 60 years are presented. The prospects and an outlook on the future development of lithium–sulfur batteries for large‐scale practical applications are also discussed and presented.